Accepting of E-banking among Banking Customers of Pakistan - Mughal, Muhammad Muazzam; ., Kamran Ali; ., Abdul Jabbar Khan (Information Management and Business Review, 2012)
E-banking is a platform through which a banking customer can perform its financial or non financial transactions electronically without visiting bank, which not only reduces transaction costs but also saves time.E-banking customers are increasing worldwide but its adoption is low in Pakistan. This study is done to investigate the most important factors which contribute to the espousal of E-banking in Pakistan. For this research primary data was collected from 217 customers of different ages, data was collected by structured questionnaire. Statistical descriptive analysis was used to analyze the data. The results shows that privacy and security, trust, ease of usefulness, knowledge and awareness, inaccessibility and came in person preferences are the factors which affect adoption of E-banking in Pakistani customers. Findings also indicate that banking customers of Pakistan are willing to take on E-banking if proper guideline and awareness is provided to them by banks or banking regularity authorities.